MODEL FORMULASI KEBIJAKAN PEMBEBASAN PAJAK BUMI DAN BANGUNAN (PBB) OLEH DPRD KOTA PALEMBANG DALAM RANGKA MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Nusantara, Adzanu Getar; Alfitri, Alfitri; Lionardo, Andries; Nadjib, Abdul (Jurnal EL-RIYASAH, 2025)
This study examines the formulation of property tax (Pajak Bumi dan Bangunan/PBB) exemption policy by the Dewan Perwakilan Rakyat Daerah (DPRD) of Palembang City in the context of improving social welfare. Using a qualitative case study approach, the research explores how the policy was formulated, the supporting and inhibiting factors, and its implications for fiscal capacity and citizens’ welfare. Data were collected through in-depth interviews, participatory observation, and document analysis, and analyzed thematically. The findings show that the policy formulation process was participatory yet compromise-based, involving DPRD, the local government, and the community. Supporting factors included political commitment, executive support, and public participation, while constraints included fiscal limitations, bureaucratic resistance, and political dynamics among DPRD factions. The results reveal that the PBB exemption policy successfully reduced the financial burden on low-income households without significantly decreasing local revenue, thereby enhancing both tax compliance and political legitimacy. This research contributes to public policy studies by demonstrating how local fiscal policies can balance social justice with fiscal sustainability.